Trabeculectomy with Mitomycin C and Intra-Ocular Pressure in Congenital Glaucoma Patients - Mohammad Aamir Khan, Shahid Anwar Bhatti, Faizan Tahir, Muhammad Imran Ali, Muhammad Aamir Shahzad, Maria Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to evaluate the mean change in intraocular pressure following trabeculectomy with Mitomycin C in patients who present with congenital glaucoma. Study Design: Observational/ Cross-sectional Place and Duration: Data was collected from different hospitals of Pakistan, including Jinnah International Hospital, Abbottabad and Department of Ophthalmology, Sahara Medical College, Narowal from December 2021 to May 2022. Methods: The study included 62 patients, both male and female, with primary congenital glaucoma, ranging in age from birth to five years. After receiving signed permission from patients' legal guardians, we were able to record their demographic information. Trabeculectomy using 0.4mg/ml Mitomycin C was performed on all of the patients. Mitomycin C was placed for 2 minutes under the scleral flap. The intraocular pressure was measured before surgery and again 12 days later. Statistical analysis was performed using SPSS 22.0. Results: Included children had mean age 1.9±3.16 years. We found that, majority of the patients 39 (62.9%) were males and 23 (37.1%) cases were females. The mean intraocular pressure before and after surgery was significantly different, with a p-value of 0.002 (29.41±5.22 Vs 15.17±1.73). Conclusion: It has been determined that doing a trabeculectomy while administering mitomycin C results in a significant decrease in intraocular pressure. Following surgery, a substantial reduction in intraocular pressure was noted by the attending physician. Keywords: Intra-ocular Pressure, Primary Congenital Glaucoma, Mitomycin C, Trabeculectomy